Utilization of GIS for Ecosystem-Based Adaptation with Community Participation in Flood Disaster Management in Pati Regency - Wijaya, Muhammad Indra Hadi; Sejati, Anang Wahyu; Arsynindia, Lutfia Diah; Junjungan, Reinhart Christopher; Kardiman, Maman Eka (Jurnal Litbang: Media Informasi Penelitian, Pengembangan dan IPTEK, 2025)
ENGLISHWatersheds are unified landscapes vulnerable to hazards like floods, often exacerbated by factors such as land-use changes and reactive disaster management. This study analyzes land cover changes and their spatial relationship to flood-prone areas using an Ecosystem-based Adaptation (EbA) approach. It integrates remote sensing with participatory methods to enhance disaster risk reduction.The research adopted a mixed-methods design, combining spatial analysis of Landsat 8 imagery (2000–2023) with qualitative data from focus group discussions (FGDs), participatory mapping, and interviews involving local communities and government stakeholders. Key variables analyzed included land cover types, spatial extent of change, proximity to rivers, elevation, and delineated flood hazard zones. The study focused on the Silugonggo River Basin in Pati Regency, Indonesia, a high-risk flood area. Results reveal a significant increase in built-up areas (to 17.18%) and a reduction in vegetation cover (forest area decreased to 7.57%), particularly in the midstream, contributing to increased runoff and flood risk. Community engagement was crucial in identifying localized flood causes and proposing adaptive strategies such as reforestation, riparian buffer zones, and improved drainage. These findings emphasize the importance of integrating EbA and community participation into disaster risk reduction planning. INDONESIADaerah aliran sungai (DAS) merupakan bentang alam yang menyatu dan rentan terhadap bahaya seperti banjir, yang sering diperparah oleh faktor-faktor seperti perubahan tata guna lahan dan penanggulangan bencana yang reaktif. Penelitian ini menganalisis perubahan tutupan lahan dan hubungan spasialnya dengan daerah rawan banjir menggunakan pendekatan Adaptasi Berbasis Ekosistem (EbA). Pendekatan ini mengintegrasikan penginderaan jauh dengan metode partisipatif untuk meningkatkan pengurangan risiko bencana. Penelitian ini mengadopsi desain metode campuran, menggabungkan analisis spasial citra Landsat 8 (2000–2023) dengan data kualitatif dari diskusi kelompok terfokus (FGD), pemetaan partisipatif, dan wawancara yang melibatkan masyarakat lokal dan pemangku kepentingan pemerintah. Variabel-variabel utama yang dianalisis meliputi jenis tutupan lahan, luas spasial perubahan, kedekatan dengan sungai, elevasi, dan zona bahaya banjir yang telah dipetakan. Studi ini berfokus pada DAS Silugonggo di Kabupaten Pati, Indonesia, sebuah daerah dengan risiko banjir tinggi. Hasil penelitian menunjukkan peningkatan signifikan pada area terbangun (menjadi 17,18%) dan penurunan tutupan vegetasi (luas hutan berkurang menjadi 7,57%), terutama di bagian tengah DAS, yang berkontribusi pada peningkatan limpasan dan risiko banjir. Keterlibatan masyarakat sangat penting dalam mengidentifikasi penyebab banjir lokal dan mengusulkan strategi adaptasi seperti reboisasi, zona penyangga riparian, dan sistem drainase yang lebih baik. Temuan ini menekankan pentingnya mengintegrasikan EbA dan partisipasi masyarakat ke dalam perencanaan pengurangan risiko bencana.